PENINGKATAN PENDAPATAN MASYARAKAT DUSUN GADING CANGKRINGAN, SLEMAN, DIY MELALUI PENYULUHAN PEMBUATAN "YOGHURT" ANEKA RASA - Ratnawati, Ratnawati; Suhandoyo, Suhandoyo (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2015)
Yoghurt making class is expected to increase the income of the people and the dairy farmers in the village of Gading, Glagaharjo, Cangkringan Sleman,YogyakartaaftertheMerapivolcanoeruption.Theactivitiesconsistof(1)surveytherealconditionofdairyfarms and the farmers in the Village Gading,Glagaharjo, Cangkringan, Sleman, Yogyakarta which was conducted on June 5,2014; (2) the TOT (Training of Trainers) for students who will assist in theyoghurt making class held on 26-28 June 2014, at Microbiology Laboratory,Faculty of Mathematics and Natural Sciences, Yogyakarta State University; and(3) training on yoghurt making to the target community that was PKK Arimbiheld on 20-21 July 2014. The participants were 25 members of the PKK. Theconclusion is that the training went well as it was planned, the participants succeededin making yoghurt with various flavors, and also designing a businessplan. The members of this community are very interested in developing a yoghurtbusinesssinceitisprospective.Inaddition,thepeopleneedassistanceforthepackagingand marketing of their products. For further program if it is possible,participants suggested that there is a training on the diversification ofmilk and yoghurt products which can be marketed as food gift from Merapitourist areas